La pollada peruana en Buenos Aires: Migración y comportamiento étnico en un contexto de conflicto urbano. Issue 4 (2nd October 2021) - Cuberos-Gallardo, Francisco J.
ABSTRACT: The Peruvian pollada is an organized practice of fundraising solidarity through the preparation and distribution of meals among informal networks of relatives and friends. Emerged fifty years ago in the context of the great migrations to the city of Lima, the pollada has consolidated itself in the Peruvian culture and assumes a veriegated set of functions. This paper discusses the reproduction of the practice by Peruvian immigrants in the Abasto neighborhood of Buenos Aires, Argentina. It provides a detailed description of the uses, forms and role of the pollada as a unique experience of Peruvians migrants in their adjustment to Argentine society. The analysis points to the importance of ethnic identity as a decisive factor in articulating forms of mutual assistance among immigrants. It also underscores the effectiveness of the pollada as an expression of ethnic behavior in the migratory context.